Evaluasi Desain Taman Islam Berdasarkan Al-Qur'an dan Hadist di Masjid Jamik Baitul Izzah, Bireuen - Rismawati; Maysarah Binti Bakri; Marisa Hajrina (Prodi Arsitektur, Fakultas Sains dan Teknologi bekerja sama dengan Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Parks are areas composed of softscape and hardscape elements that not only beautify the environment, but also maintain its sustainability and quality, and function as a gathering place for people to enjoy the outdoors. The presence of parks can be seen in various architectural features, including in mosques. Generally, the concept of a mosque garden is an Islamic garden to maintain continuity with the theme of the building design. One of the mosques designed for its outdoor area and garden is the Jamik Baitul Izzah Mosque located in Kutablang District, Bireuen.